PENGARUH PENAMBAHAN SERAT KARUNG PLASTIK PADA TANAH LEMPUNG TERHADAP UJI CBR - ROLENSI WULANDARI; Suradji Gandi; Fatma Sarie (Program Studi Teknik Sipil Universitas Narotama, 2022)
The island of Kalimantan is dominated by clay soil which makes construction on buildings and roads experiencing problems in development, therefore research is needed to determine what type and classification of soil is. To improve the soil properties by stabilizing it using the CBR test mixed with additives such as wood charcoal powder, and plastic sack fiber. know the value of swelling (swelling). The percentage of mixture for wood charcoal powder is 4% and the percentage variation of the mixture of plastic sack fiber is 0.2%, 0.4%, and 0.8%. Based on the results of the study, the original soil CBR value was 4.40%, after adding the CBR mixture variation, the CBR value changed. In the 0.2% mixture variation the CBR value increased to 5.30% of the original soil CBR value. Then for the mixed variation of 0.4% the CBR value increased to 5.60% of the original soil CBR value. And for the mixed variation of 0.8% the CBR value increased to 6.00% of the original soil CBR value. The highest CBR value is clay with a mixed variation of 0.8% with a CBR value of 6.00%. Furthermore, the results obtained from the CBR value of the immersion with the original soil CBR value of 0.85% with a swelling value of 7.4202%. And the highest immersion CBR value for the mixture was found in the mixed variation of 0.8% with the Immersion CBR value of 1.50% and the swelling value decreased to 4.6956%. From these results, the addition of wood charcoal powder and plastic sack fiber can stabilize the CBR of clay soil. Keywords: Wood Charcoal Powder, CBR (California Bearing Ratio), Plastic Sack Fiber, Clay Soil.